Criminal Liability of Minors for Offenses in the Field of Informatization and Communications - Halibiyati, H.; Amirov , N.K.; Adilgazy, S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines issues of the legal responsibility of minors for administrative and criminal offenses in the field of informatization and communications in the context of rapid digitalization. The purpose of the study is to analyze the specific features of holding minors legally liable for offenses in the digital environment and to develop scientifically grounded recommendations for improving legislation and law enforcement practice, taking into account age-related, psychological, and social characteristics. The methodological framework is based on general scientific and special legal methods, including analysis and synthesis, induction and deduction, formal legal and comparative legal methods, as well as the analysis of statistical data and law enforcement practice in the Republic of Kazakhstan and selected foreign jurisdictions. The results show that minors’ involvement in digital offenses is driven by technological accessibility, insufficient legal and digital culture, and psychological immaturity associated with incomplete legal awareness. The scientific value of the study lies in the systematization of approaches to juvenile liability for cyber offenses. The practical significance consists in the applicability of the findings to preventive programs, educational initiatives aimed at improving adolescents’ legal and digital culture, and the further development of legislation and law enforcement practice in the field of informatization and communications.